Men's triathlon correlation between stages and final result in the London 2012 Olympic Games - Fernández-Revelles, A. B.; Ramírez-Granizo, I.; Castro-Sánchez, M.; Padial-Ruz, R. (Journal of Human Sport & Exercise, 2018)
Introduction: Triathlon is a sport that combines three different disciplines. The most widespread triathlon is the Olympic modality, which is used in the Olympic Games, consisting of swimming 1.5 km, cycling 40 km and running 10 km. Aims: To determine the influence of the duration and order of the different stages on the final result of the men`s triathlon race in London 2012 Olympic Games. Method: Data from 54 athletes who finished was analysed. Results and conclusions: The final result is not determined neither by the order of the stages, nor by their duration, the least influential discipline being Bike without correlation with result; however being the most time consuming, 53.76%; the most influential stage was Run with rs = 0.913; and p = 0.000; and R2 =0 .833, with 28.93% duration